2006
DOI: 10.1785/0120050233
|View full text |Cite
|
Sign up to set email alerts
|

Recent and Long-Term Behavior of the Brawley Fault Zone, Imperial Valley, California: An Escalation in Slip Rate?

Abstract: The Brawley fault zone (BFZ) and the Brawley Seismic Zone constitute the principal transfer zone accommodating strain between the San Andreas and Imperial faults in southernmost California. The BFZ ruptured along with the Imperial fault in the 1940 M w 6.9 and the 1979 M w 6.4 earthquakes, although in each case only minor slip apparently occurred on the BFZ; several other episodes of slip and creep have been documented on the BFZ historically. Until this study, it has been unclear whether the past few decades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…We estimate that the extension within the Mesquite Basin corresponds to 13.8 ± 3.0 mm/yr of subsidence (using a 75° dip angle estimated from Chen and Shearer []), which is roughly in line with estimates of vertical creep since the 1970s along the Brawley Fault from fault trenching by Meltzner et al . [].…”
Section: Resultssupporting
confidence: 91%
“…We estimate that the extension within the Mesquite Basin corresponds to 13.8 ± 3.0 mm/yr of subsidence (using a 75° dip angle estimated from Chen and Shearer []), which is roughly in line with estimates of vertical creep since the 1970s along the Brawley Fault from fault trenching by Meltzner et al . [].…”
Section: Resultssupporting
confidence: 91%
“…Fault scarps are not visible at the surface, so we assume that sedimentation rates are equivalent to or greater than slip rates on high‐angle normal faults averaged over geologic time, which implies that subsidence rates associated with faulting cannot be greater than the highest sediment accumulation rate. While sedimentation rates across the ST generally vary from 2 to 11 mm yr −1 [ Van De Kamp , ; Meltzner et al , ; Dorsey , ], robust late‐Holocene rates of ∼20 mm yr −1 have been observed [ Brothers et al , ] at the depocenter, underneath the Salton Sea, and ∼10 km to the northwest of Obsidian Butte. Slip rates on potentially active structures southeast of the depocenter, toward our model faults, cannot be determined through marine seismic methods because of active CO 2 degassing, as we mentioned before and are wholly unconstrained by geodetic data.…”
Section: Discussionmentioning
confidence: 99%
“…18) are potentially consistent with the Coachella lake chronology, given the dating uncertainties. Incomplete and less well-dated lake chronologies have been reported from the Superstition Mountain (Gurrola and Rockwell, 1996), International Border (Thomas and Rockwell, 1996), and Brawley (Meltzner et al, 2006) paleoseismic sites (see locations on Fig. 1b), at the 12-m highstand shoreline, 9 m elevation, and 37 m, respectively.…”
Section: Lake Chronologiesmentioning
confidence: 91%